Polysémie, prototype et invariant : le cas du verbe « manger » en dagara - Pénou-Achille Somé (Corela, 2007)
In Dagara, the most common translation for the verb di is « eat ». Other translations, however, are: “spending, taking advantage of” and, more surprisingly, that of “burning, wearing out, hurting, being infected…”, but also “be named x, look like x”, then “be x only by name” or, on the contrary, “be topmost, reach the target, make good for a bad situation”. For each of these meanings, “di” always differs from its false-synonyms (munch, blaze, wear, hurt… call, be or have, resemble, manage, make up for…). We distinguish two main types, one where di is a verb of accomplishment, and one where di is a verb of state. In both cases, the meanings are classified according to the nature of the subject and of the complement. The investigation gradually reveals how the grammatical structure fits with the semantics as well as the ethnological data, mainly through a constant valuation of the state of affairs by the Speaker. After a brief discussion on the cognitivist vs constructivist approaches, the article concludes by showing how all of the meanings can be united around a single common, abstract schema.